2005
DOI: 10.1111/j.1432-2277.2004.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

C2 is superior to C0 as predictor of renal toxicity and rejection risk profile in stable heart transplant recipients

Abstract: Summary To assess whether cyclosporine A (CsA) 2‐h peak (C2) is superior to trough levels (C0) for Neoral dose monitoring in heart transplantation (HT), we studied 928 C0–C2 paired determinations from 313 stable HT patients (257 male, aged 50 ± 14 years at HT, follow‐up 6.9 ± 4 years), on a C0‐based regimen. Our target C0 levels (ng/ml) were 150–400 (first 3 months), 150–300 (4–12 months), 100–250 (>12 months). Mean C0 and C2 levels were 268 ± 80 and 1031 ± 386, respectively (first 3 months); 230 ± 49 and 955 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In renal, liver and heart transplant patients, there is already increasing evidence that C 2 not only correlates well with the AUC 0-4 h , and that C 2 monitoring to ensure adequate levels resulted in lower incidences of rejection and nephrotoxicity. [4][5][6][7][8]10,12,13 Unfortunately, there are no data to our knowledge about C2 monitoring among HSCT recipients. In our study, short infusion of CsA resulted in C2 levels X800 mg/l in 20 of 24 (83%) patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In renal, liver and heart transplant patients, there is already increasing evidence that C 2 not only correlates well with the AUC 0-4 h , and that C 2 monitoring to ensure adequate levels resulted in lower incidences of rejection and nephrotoxicity. [4][5][6][7][8]10,12,13 Unfortunately, there are no data to our knowledge about C2 monitoring among HSCT recipients. In our study, short infusion of CsA resulted in C2 levels X800 mg/l in 20 of 24 (83%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…C 2 monitoring is also associated with clinical benefits like a reduction in graft rejections after solid organ transplantation. [4][5][6][7][8][9][10][11][12][13] Surprisingly, data on pharmacokinetics and target C 2 levels are lacking in HSCT patients. Moreover, there is no consensus about how CsA should be administered with some centres giving 1 or 2 intermittent infusions and others continuous 24 h infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with data from studies in for example heart transplant recipients, dose-related C2 seems to be lower in our HSCT patients (191 and 160 ng/ml/mg/kg), which can probably be related to poorer absorption, as discussed above. Cantarovich et al 4 reported a mean C2/dose of 278 ng/ml/mg/kg and Caforio et al 7 a mean of 250 ng/ml/ mg/kg. In patients with sibling donors, the median C0 during the first month after transplantation was found to be considerably higher (141 ng/ml) than the aim (100 ng/ ml), whereas in patients with MUD, the median C0 of 274 ng/ml was within the desired range of 250-300 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, concentration sampling 2 h after dose intake (C2) has been suggested as a better measure of both total drug exposure and effect in kidney, heart and liver transplant patients. [4][5][6][7] In other series of liver and heart transplant patients, no clinical superiority (lower incidence of acute graft rejections) was demonstrated using C2 levels. 8,9 A definite drawback of C2 measures is that they are sensitive to minor deviations in sampling time.…”
Section: Introductionmentioning
confidence: 99%
“…No data exist in the pediatric heart transplant recipients. Randomized trials [83,84] addressed the clinical significance of C2 monitoring in adult heart transplant recipients and did not demonstrate an advantage of C2 monitoring in preventing renal impairment [85]. Some pediatric (non-cardiac) nonrandomized trials have correlated C2 to acute rejection occurrence [86], but no current data exist about the advantage of C2-monitoring to prevent CNI-induced nephrotoxicity in the pediatric population.…”
Section: Cni Avoidancementioning
confidence: 98%